PERANCANGAN ARTISTIK PANGGUNG PERTUNJUKAN TEATER NASKAH â€œMUSUH MASYARAKATâ€ KARYA HENRIK IBSEN - Kurniawan, Fajar; Sriwardani, Nani; Emilda, Nia (ATRAT: Jurnal Seni Rupa, 2021)
The artistic design of the stage that uses the script of the enemy of society as a reference has a common thread that helps in the visualization process, namely: the setting of the place and the atmosphere of the script story is in the 1810-1954 era which is the Victorian era, this era is famous for its luxurious atmosphere because it focuses on the aesthetics of the shape in the building , fashion and space layout. This era also has a characteristic form of ornament, non-flat shape and tassels that symbolize luxury. This stage artistic design method is carried out through 3 processes: design, visualization and presentation. This stage artistic design has a purpose: adapting stage arts in free interpretation, creating an impression of symbolic interpretation in stage visuals and properties and giving new references in stage artistic design.The results of the artistic design of the theater stage for the enemy of society's script are presented in the form of a multilevel stage and supporting properties that add to the symbolic impression and can add to the vocabulary in the field of stage layout.Â Keywords: Manuscript, Victorian Era, Luxury, Symbolic, Performance Stage.------------------------------------------------------------------------------------------Perancangan artistik panggung yang menggunakan naskah musuh masyarakat sebagai acuan memiliki benang merah yang membantu dalam proses visualisasi yaitu : latar tempat dan suasana cerita naskah terdapat diera 1810-1954 yang merupakan era Victoria, era ini terkenal dengan suasana mewahnya karena menitik utamakan kepada estetik bentuk dalam bangunan, fashion dan tata letak ruang. Era ini juga memiliki ciri khas yang berupa ornament, bentuk yang tidak flat dan rumbai-rumbai yang menyimbolkan kemewahan. Metode perancangan artistik panggung ini dilakukan melalui 3 proses: perancangan, visualisasi dan penyajian. Perancangan artsitik panggung ini memiliki tujuan : pengadaptasian artsitik panggung dalam tafsir bebas, menimbulkan kesan tafsir simbolis dalam visual panggung dan property dan memberi referensi baru dalam perancangan artistik panggung.Â  Hasil perancangan artistic panggung teater naskah musuh masyarakat ini disajikan dalam bentuk panggung bertingkat dan property pendukung yang menambah kesan simbolis dan dapat menambah perbendaharaan dibidang tata pentas.Â Kata kunci: Naskah, Era Victoria, Mewah, Simbolis, Tata Pentas.Â